MAKING INFORMATION SECURITY STRATEGIC TO BUSINESS - A. R. Yuldashev, S. M. Turdaliyev (Galaxy International Interdisciplinary Research Journal, 2022)
This article outlines issues aimed at making information security strategic for business and promoting akhbototot despair in a growing society.